Leydig cell tumor of the ovary: A case report (Research, Society and Development, 2023)
Leydig cell tumors of the ovary are classified as benign androgen-secreting neoplasms, which are often related to complaints of virilization in postmenopausal women. However, they represent less than 0.5% of all ovarian tumors and, because of this, their diagnostic description and management are still scarce. The present study aims to contribute to the understanding of the pathology and gather tools to improve care, diagnosis, conduct and contribute to the theoretical collection, introducing debates on its theory and medical conduct, progressing in the quality of care, emergence of hypotheses and adequate management and frame early. We present the case of a patient, female, 34 years old, with complaints of amenorrhea, alopecia, increased libido, deep voice, hirsutism and clitoral hypertrophy. Together, the laboratory evaluation with high levels of total testosterone associated with Magnetic Resonance with oval nodular formation in the left adnexal region, led to surgical treatment. Thus, the patient underwent left salpingo-oophorectomy, which led to the histopathological result in question.